LOCATION AND DEVELOPMENT OF INDUSTRIAL SECTORS IN THE REGIONS - Shohzakhon Nodirbek ugli, Mahmudov («YANGI O’ZBEKISTON IQTISODIYOTI», 2026)
This article provides an in-depth analysis of the economic, technological, and regional factors affecting the development of the textile industry. It also explores evaluation criteria for these factors and their impact on sectoral efficiency. The findings offer insights for shaping advanced strategies in textile sector development.